2021
DOI: 10.33774/chemrxiv-2021-d0fg9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multifunctional Polyoxometalate-Platforms for Supramolecular Light-driven Hydrogen Evolution

Abstract: Multifunctional supramolecular systems are a central research topic in light-driven solar energy conversion. Here, we report a polyoxometalate (POM)-based supramolecular dyad, where two platinum-complex hydrogen evolution catalysts are covalently anchored to an Anderson polyoxomolybdate anion. Supramolecular electrostatic coupling of the system to an iridium photosensitizer enables visible light-driven hydrogen evolution. Combined theory and experiment demon-strate the multifunctionality of the POM, which acts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The variation of the linkage structure caused fundamental changes in the excited-state topology of the dyads and orders of magnitude changes in the intramolecular electron transfer rates and excited-state lifetimes [65] . Pt(II)-complex were also used to covalent attach with Anderson-type platform-POMs for HER [66] . The results showed that POMs acted as PS-and catalyst-binding sites, facilitating electron transfer under irradiation.…”
Section: Photocatalysismentioning
confidence: 99%
“…The variation of the linkage structure caused fundamental changes in the excited-state topology of the dyads and orders of magnitude changes in the intramolecular electron transfer rates and excited-state lifetimes [65] . Pt(II)-complex were also used to covalent attach with Anderson-type platform-POMs for HER [66] . The results showed that POMs acted as PS-and catalyst-binding sites, facilitating electron transfer under irradiation.…”
Section: Photocatalysismentioning
confidence: 99%
“…As shown in several previous reports, replacement of the chloride ligands by iodide ligands typically enhances lightinduced hydrogen evolution in Pt-based systems. 19,48,49 For instance, Kaufhold et al 48 showed that the addition of an iodide salt to the photocatalytic system can activate a platinum center during photocatalysis by in situ ligand exchange leading to improved H 2 formation.…”
Section: Light-induced Evolution Of Molecular Hydrogenmentioning
confidence: 99%
“…This work is therefore relevant to the growing area of molecular spintronics, as well as the important topic of structure prediction for molecular materials in general. While bifunctional and multifunctional molecular assemblies have been reported in the experimental literature previously, [ 29,30 ] the prediction of a bifunctional assembly entirely from computation appears to be a first.…”
Section: Introductionmentioning
confidence: 99%